2016
DOI: 10.1038/srep22041
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Foundations of Sp110-mediated Macrophage (RAW264.7) Resistance to Mycobacterium tuberculosis H37Ra

Abstract: Human tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a leading global health problem, causing 1.3 million deaths each year. The nuclear body protein, Sp110, has been linked to TB resistance and previous work showed that it enhances macrophage apoptosis upon Mtb infection. Here, we report on the role of Sp110 in transcriptional regulation of macrophage responses to Mtb through integrated transcriptome and mechanistic studies. Transcriptome analysis revealed that Sp110 regulates genes inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 53 publications
(83 reference statements)
1
34
0
Order By: Relevance
“…Our group recently performed small RNA sequencing and found that M. tuberculosis H37Ra (H37Ra) induced the expression of the cluster of miR-23b/27b (11). We hypothesized that the cluster of miR-23b/miR-27b/miR-24-1 could be regulated by M. tuberculosis.…”
Section: Mir-27b Is Upregulated Post-m Tuberculosis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently performed small RNA sequencing and found that M. tuberculosis H37Ra (H37Ra) induced the expression of the cluster of miR-23b/27b (11). We hypothesized that the cluster of miR-23b/miR-27b/miR-24-1 could be regulated by M. tuberculosis.…”
Section: Mir-27b Is Upregulated Post-m Tuberculosis Infectionmentioning
confidence: 99%
“…We previously investigated the role of miRNAs in M. tuberculosis H37Ra infection using small RNA sequencing, which suggested that M. tuberculosis H37Ra induces the expression of miR-27b (11). In the current study, we investigated the potential role of miR-27b in regulating macrophage apoptosis and inflammatory response during M. tuberculosis infection.…”
mentioning
confidence: 96%
“…More than 30% of the world population is infected with Mtb , but less than a tenth of these individuals is at risk of developing overt clinical symptoms [ 1 ], suggesting that the innate immune system plays a crucial role in the defense against Mtb . Previous studies found that mouse intracellular pathogen resistance 1 (Ipr1, also known as Speckled 110 KDa protein) mediates innate immunity to Mtb and that overexpression of Ipr1 limits bacterial proliferation and reactivates the apoptotic pathway of Mtb -infected mouse macrophages [ 2 , 3 ]. Moreover, polymorphisms of the human homologue of the mouse Ipr1 gene ( Sp110 ) are associated with tuberculosis susceptibility [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Sp110c, detected specifically in human peripheral blood leukocytes and spleen, is known to activate RAR␣-mediated transcription (9,10). Sp110 is reported to be associated with the hepatic veno-occlusive disease with immunodeficiency (VODI) (11), acute promyelocytic leukemia (8), and tuberculosis (12)(13)(14)(15)(16). A study showed that Sp110b interacts with hepatitis C virus core protein and gets relocalized from the nucleus to the cytosol (mainly near the endoplasmic reticulum membranes).…”
mentioning
confidence: 99%